PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATKAN KETERBUKAAN DIRI SISWA KELAS X MIA SMA NEGERI 1 PEKANBARU TAHUN AJARAN 2015/2016 - Cici Adesia Rosade; Rosmawati '; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Self-disclosure is part of the communication. Students should have the skills in communication. Difficulty in performing self-disclosure will make the students have difficulty in communicating with others. This study aims to determine the effect of group guidance towards increased self disclosure of the students, especially students of class X MIA SMA Negeri 1 Pekanbaru. This type of research is True Experiment with the Control group pretest and posttest design. Subjects in this study were 20 students with lower levels of self-disclosure. From the results of data analysis using Wilcoxon test with SPSS 16 is obtained α= 0.005.α value less than 0.05 (0.005 <0.05), it can be concluded that there are significant differences levels of self-disclosure with the students before and after being given guidance services group. This means that students self-disclosure can be enhanced through group counseling. Mann Whiteney of test results between the experimental group and the control group with SPSS 16 is obtained α = 0,000. α value less than 0.05 (0.000 <0.05), From these results concluded that there are significant differences between the experimental group and the control group on the post test results. That is the result of post test experimental group is better than the control group.The effect of group guidance to increase self-disclosure at 44.7%.Key Words : Guidance Group, Self Disclosure.